THE EFFECT OF LOCAL GOVERNMENT REVENUE (LGR), BALANCE FUND, CAPITAL EXPENDITURE AND FISCAL STRESS ON THE FINANCIAL PERFORMANCE OF REGIONAL GOVERNMENT IN THE DISTRICT / CITY OF SUMATERA UTARA PROVINCE - Malau, Eve Ida (International Journal of Public Budgeting, Accounting and Finance, 2019)
The purpose of this study was to analyse the effect of local government revenue (LGR), balance funds, capital expenditure, and fiscal stress partially on the financial performance of local governments in the districts / cities of North Sumatra Province. The population of this study is the regency / city of North Sumatra Province as many as 33 districts / cities with the observation year 2010 to 2017. Samples using saturated samples where the population as the sample. Data is processed using panel data regression statistical test methods. The results of this study prove that local government revenue (LGR), balance funds, and fiscal stress partially affect the financial performance of local governments in the districts / cities of North Sumatra Province. While capital expenditure does not affect the financial performance of regional governments in the districts / cities of North Sumatra Province.